(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
The use of artificial intelligence in teaching chemistry in high schools makes it possible to radically change the educational process today. The science of chemistry is characterized by its complex theory, numerous formulas, reactions and experiments. As well as helping students delve deeper into the basics of science, this science also presents many challenges. Therefore, the use of modern technologies in the educational process, in particular artificial intelligence, is important in facilitating and improving the effectiveness of the learning process of students.